1992
DOI: 10.1007/bf00044167
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic microorganisms: processes, populations, and molecular solutions to environmental problems

Abstract: Studies on aquatic ecosystems at the trophic level of bacteria include population succession and the movement of species through the water column. Factor and path analysis of environmental parameters and the bacterial profiles indicate that the bacterial populations are under the control of environmental factors. The most important environmental factors in the Canadian study reported here are temperature followed by oxygen levels, nutrient levels, and ion concentrations. A major revolution in investigative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The path analysis indicated that the predominant population was controlled by environmental influences. [Holder-Franklin 1992].…”
Section: Monitormentioning
confidence: 99%
“…The path analysis indicated that the predominant population was controlled by environmental influences. [Holder-Franklin 1992].…”
Section: Monitormentioning
confidence: 99%
“…Abiotic variables, such as availability of nutrients and pollution, may determine bacterial abundance in river water [2]. Evidence is accumulating that bacteria are the pivotal group in the biodegradation and bioremediation of any ecosystem [3]. Thus, the degradation of contaminants in river water is essentially catalyzed by microbes and needs an active microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Chemostat experiments were then initiated to study competition between river strains for nutrients (Bell et al, 1982). This was extended to a cause and effect study using path analysis -an algorithm which clearly demonstrated that the bacteria were completely controlled by the environment (Holder-Franklin, 1992). Two tributaries of the St. John River were added to the study sites.…”
Section: Introductionmentioning
confidence: 99%